2019
DOI: 10.3892/ol.2019.11027
|View full text |Cite
|
Sign up to set email alerts
|

Association between breast cancer cell migration and radiosensitivity in�vitro

Abstract: The aim of the present study was to examine the association between the migration of breast cancer cells in vitro and radiosensitivity by establishing a breast cancer cell model with different migratory capacities. Transwell chambers in a 24-well plate were used to separate MDA-MB-231 and ZR-7530 cells and to establish cell models with different migratory capacities. Subsequently, the radiosensitivity of the cell models was measured using a radiation clone formation assay. Furthermore, differential gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…As FN1 is highly expressed in tumor vessels and mediates angiogenesis during tumorigenesis, it also plays important roles in cancer progression. It has been reported that FN1 is highly expressed in breast cancer ( 16 ), nasopharyngeal carcinoma ( 17 ), oral squamous cell carcinoma ( 11 ) and thyroid carcinoma ( 18 ), and plays a regulatory role in the major inflammatory cells present in the tumor microenvironment. In addition, FN1 expression is significantly upregulated in uterine leiomyoma and is associated with trophoblast invasion, uterine proliferation and adhesion function ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…As FN1 is highly expressed in tumor vessels and mediates angiogenesis during tumorigenesis, it also plays important roles in cancer progression. It has been reported that FN1 is highly expressed in breast cancer ( 16 ), nasopharyngeal carcinoma ( 17 ), oral squamous cell carcinoma ( 11 ) and thyroid carcinoma ( 18 ), and plays a regulatory role in the major inflammatory cells present in the tumor microenvironment. In addition, FN1 expression is significantly upregulated in uterine leiomyoma and is associated with trophoblast invasion, uterine proliferation and adhesion function ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“… 27 A number of studies have shown that the development of EMT and CSCs following radiotherapy promotes the ability of breast cancer cells to acquire metastatic properties. 1 , 28 , 29 , 30 This mechanism was recognized as a limitation of single radiation therapy 31 , and the need for a new treatment strategy to prevent metastasis and recurrence was emphasized. Small molecules inhibiting TGF-β/ALK5 kinase, vactosertib effectively inhibited lung metastasis from breast cancer in a mouse model and has been investigated in various ongoing clinical trials with cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most simplistic model of in vitro cancer research is a two-dimensional (2D) monolayer culture of cancer cell lines, which, in spite of being the most utilized model, cannot provide realistic data about the heterogeneous, multicellular tumor microenvironment (TME) in the body. Currently, various models such as animals [2,3], transwells [4], spheroids [5][6][7][8], organoids [8][9][10], and xenografts [11,12] are utilized in cancer research with many advantages and disadvantages [13,14]. Hence, there is a need to develop models that can be utilized for monitoring cell growth, viability, polarization, and differentiation, as well as for and studying migration and invasion of tumor cells into the surrounding TME.…”
Section: Introductionmentioning
confidence: 99%